Digital Promotion Strategy to Increase Archival Institution Visibility: Content Analysis of the Universitas Indonesia Archival Office’s YouTube Channel - Ade Maya Azkiyati; Muhamad Prabu Wibowo (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2026)
Background: In the era of digital transformation, archival institutions are required to not only manage administrative documents but also to build a more strategic and representative institutional image. The use of social media, such as YouTube, Instagram, or Facebook, becomes a strategic tool to build brand visibility and expand an institution’s public communication reach.Objective: This study aimed to analyze strategies for increasing the visibility of the UI Archives Office through social media. The study focuses on the types of YouTube content published by the Universitas Indonesia (UI) Archives Office and audience engagement with the posted uploads.Methods: The units of analysis include content themes, information presentation, audience engagement, and their potential contribution to strengthening the visibility of the UI Archive Office.Results: The study found that despite the educational and informative content presented, the UI Archives Office’s YouTube channel has not optimally built a strong visual narrative or engaged audience participation. The visual narrative used tends to be formal and lacks the use of Call-to-Action (CTA) elements that could build an emotional connection with the audience.Conclusion: These results indicate that YouTube has great potential as a branding medium for institutions, but it requires a more strategic and participatory digital communication approach. Strategic recommendations are provided through increasing the Call-to-Action (CTA) elements in every video uploaded, involving students and alumni to expand the audience reach, cross-media social integration, and organizing internal training related to digital content management. Further research should focus on measuring whether increased visibility through social media contributes to an increase in archival literacy, the utilization of archival services, or public participation in institutional activities. Keywords: YouTube; content analysis; audience engagement; and visibility